QUILOMBOLA COMMUNITIES: speeches and disputes over territorial rights - Lacerda Jorge, Amanda; Pereira Brandao, André Augusto (Universidade de Brasília, 2021)
In the quest to contribute to reflections on the territorial law of traditional peoples and communities such as quilombolas, this article aims to discuss the interpretive dispute in the legal field about the title and demarcation of the territories that belong to these groups. The study addresses the Direct Action of Unconstitutionality (ADI) 3239/2004 brought by the Democratic Party against Decree No. 4887/2003 (which regulates the process of territorial titling of quilombola communities). The proposed investigation was based on a bibliographic survey and mainly on the documentary analysis of the records of the trial process. By mobilizing a large number of internal and external agents in the legal field, ADI 3239/2004 had a long process in the Supreme Federal Court, with a high degree of exposure to interpretive conflicts, which were finalized in the final judgment, which occurred in February 2018. The context in question brought perplexity and new questions to the field of law and to society in general, putting on the scene issues related to the guarantee of the fundamental right to life, the material, cultural, social and symbolic reproduction of these peoples.